Modeling Demand for a Telecommunication Utility Operator Based On the Box-Jenkins Methodology - Botchey, Francis Effirim (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Science in Telecommunications Engineering, May-2012